2013
DOI: 10.1111/1440-1681.12100
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse traumatic brain injury and the sensory brain

Abstract: In this review we discuss the consequences to the brain's cortex, specifically to the sensory cortex, of traumatic brain injury. The thesis underlying this approach is that long-term deficits in cognition seen after brain damage in humans are likely underpinned by an impaired cortical processing of the sensory information needed to drive cognition or to be used by cognitive processes to produce a response. We take it here that the impairment to sensory processing does not arise from damage to peripheral sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 139 publications
(219 reference statements)
3
32
0
Order By: Relevance
“…The effects of TBI may also be exerted through inflammatory processes: as we have noted previously (Alwis et al, 2013), activation of inflammatory cascades as part of the normal cellular response to injury can cause further injury to the already damaged brain (Menge et al, 2001; Morganti-Kossmann et al, 2002). The inflammatory response in TBI involves production of pro-inflammatory cytokines like interleukin-1 (IL-1), IL-6 and tumor necrosis factor (TNF-a), and anti-inflammatory cytokines such as IL-10 and IL-12, all of which are seen in the cerebrospinal fluid of TBI patients within a few hours of the primary injury.…”
Section: Mechanisms Promoting Improved Behavioral and Pathological Rementioning
confidence: 87%
See 1 more Smart Citation
“…The effects of TBI may also be exerted through inflammatory processes: as we have noted previously (Alwis et al, 2013), activation of inflammatory cascades as part of the normal cellular response to injury can cause further injury to the already damaged brain (Menge et al, 2001; Morganti-Kossmann et al, 2002). The inflammatory response in TBI involves production of pro-inflammatory cytokines like interleukin-1 (IL-1), IL-6 and tumor necrosis factor (TNF-a), and anti-inflammatory cytokines such as IL-10 and IL-12, all of which are seen in the cerebrospinal fluid of TBI patients within a few hours of the primary injury.…”
Section: Mechanisms Promoting Improved Behavioral and Pathological Rementioning
confidence: 87%
“…There are two major forms of TBI—focal and diffuse. Focal brain injury is caused by direct, localized damage to the brain, while diffuse injury is most commonly caused by indirect forces, such as during rapid acceleration/deceleration of the head (Andriessen et al, 2010; Alwis et al, 2013). TBI affects approximately 2 million individuals every year in the US alone (Faul et al, 2010) and has been shown to result in a number of persistent sensory deficits, which are thought to underlie TBI-associated cognitive disabilities (Caeyenberghs et al, 2009; Davis and Dean, 2010; Lew et al, 2010; Folmer et al, 2011).…”
Section: Ee and The Damaged Brainmentioning
confidence: 99%
“…CR acts as a Ca 2+ buffer (Schwaller et al, ), regulating dendritic Ca 2+ transients (Edmonds et al, ) and affecting pre‐ and postsynaptic Ca 2+ signaling to ensure synchronization and synaptic plasticity in neuronal networks. In TBI there is excessive extracellular glutamate, resulting in overstimulation of neurons and glia, causing increased Ca 2+ , Na + , and K + fluxes (Alwis et al, ). The Ca 2+ influx triggers a cascade of cellular events culminating in cell death (Cotman and Iversen, ).…”
Section: Discussionmentioning
confidence: 99%
“…6 The processes leading to injury can be classified as primary and secondary injury mechanisms. [7][8][9][10][11] Primary mechanisms are attributed to mechanical events during impact with the brain and include brain contusion, hematomas, hemorrhage, and axonal disruption. [11][12][13] These events are followed by secondary injury processes that manifest over hours to days 14 and involve dynamic cascades that induce ionic imbalances, excitotoxicity, oxidative stress, hypoxia-ischemia, inflammation, and cerebral edema.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] These events are followed by secondary injury processes that manifest over hours to days 14 and involve dynamic cascades that induce ionic imbalances, excitotoxicity, oxidative stress, hypoxia-ischemia, inflammation, and cerebral edema. 8,9,11,15 For patients who survive the primary insults, mortality and functional outcomes are compounded by the secondary injury processes and the extent of their progression. 10 Very little is known about how the primary and secondary injury processes (and their interactions) affect the neuronal responses that underlie behavior.…”
Section: Introductionmentioning
confidence: 99%